The effect of wearing a cap on the swimmer passive drag - Marinho, D. A.; Mantha, M. R.; Rouboa, A. I.; Vilas-Boas, J. P.; Machado, L.; Barbosa, T. M.; Silva, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to analyse the effect of wearing a cap on swimmer passive drag. A computational fluid dynamics analysis was carried-out to determine the hydrodynamic drag of a female swimmer's model: (i) wearing a swimming cap and; (ii) with no cap. The three-dimensional surface geometry of a female swimmer's model with cap and with no cap was acquired through standard commercial laser scanner. Passive drag force and drag coefficient were computed with the swimmer in a streamlined position. Higher hydrodynamic drag values were determined when the swimmer was with no cap in comparison with the situation when the swimmer was wearing a cap. In conclusion, one can state that wearing a swim cap may positively influence swimmer's hydrodynamics.